(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The interpretation and application of hadith often lead to disagreements among Islamic scholars, showcasing the richness and complexity of Islamic jurisprudence. This study aims to analyze the disagreements regarding hadith in “Al-Hidaya,” highlighting key points of contention, underlying principles, and their implications for contemporary Islamic jurisprudence. Utilizing qualitative analysis, historical context, and comparative methodologies, this research draws from primary sources, including the original text of “Al-Hidaya,” and secondary sources such as scholarly articles, commentaries, and historical records. Comparative analysis with other seminal works, such as “Al-Muwatta” by Imam Malik and “Al-Umm” by Imam Shafi’i, reveals the unique contributions of “Al-Hidaya” to the science of legal disagreements (hilyaf). The findings illustrate “Al-Hidaya’s” systematic and detailed approach in addressing legal disagreements, promoting legal tolerance, inclusivity, and adaptability, thereby making it an enduring and influential resource for contemporary scholars and practitioners.